Winter Saeculum - Emil Mihalina; Ivan Krivicic; Tihomir Antunovic (UTMS Journal of Economics, 2017)
Accumulated imbalances in the economy and on the markets cause specific financial market dynamics that have formed characteristic patterns kept throughout long financial history. In 2008 Authors presented their expectations of key macroeconomic and selected asset class markets developments for period ahead based on Saeculum theory. Use of term Secular describes a specific valuation environment during prolonged period. If valuations as well as selected macro variables are considered as a tool for understanding business cycles then market cycles become much more obvious and easily understandable. Therefore over the long run, certain asset classes do better in terms of risk reward profile than others. Further on, there is no need for frequent portfolio rebalancing and timing of specific investment positions within a particular asset class market. Current stage in cycle development suggests a need for reassessment of trends and prevailing phenomena due to cyclical nture of long lasting Saeculums. Paper reviews developments in recognizable patterns of selected metrics in current Winter Saeculum dominated with prevailing forces of delivering, deflation and decrease in velocity of money.
Keywords: G11; G17; 330; asset allocation; portfolio rebalancing; asset class performance; market cycle; asset class bubbles